After Physics. - Albert, David Z. (Harvard University Press, 2015)
Here the philosopher and physicist David Z Albert argues, among other things, that the difference between past and future can be understood as a mechanical phenomenon of nature and that quantum mechanics makes it impossible to present the entirety of what can be said about the world as a narrative of "befores" and "afters."